CHIKUNGUNYA, SCRUB TYPHUS MONO, AND CO-INFECTION AMONG PATIENTS WITH UNDIFFERENTIATED FEBRILE ILLNESS: A HOSPITAL-BASED STUDY - Datta, Pratiti; Roy, Subhenjit; MANDAL, TK; Haldar, Piyali; Dan, Utpal; Saha, Santanu; Sarkar, Sumantra (Innovare Journal of Medical Sciences, 2023)
Objectives: Chikungunya virus is a common arthropod-related acute febrile disease and it is transmitted by Aedes aegypti or Aedes albopictus species. On the other hand, the bacterium Orientia tsutsugamushi causes scrub typhus, which is also an acute febrile illness with multiple organ involvement. Coinfection of chikungunya and scrub typhus may lead to severe manifestation including severe respiratory and central nervous system (CNS) complications. Coinfection of chikungunya and scrub typhus may lead to severe manifestation including severe respiratory and CNS complications. Therefore, the proper diagnosis can prevent the clinical complications. The aim and objective of our study is to find the seroprevalence of chikungunya and scrub typhus and coinfection of both through medical assessment and serological research of these patients presented with acute febrile infection at Diamond Harbour Government Medical College and Hospital. Methods: A prospective study was conducted from August 2022 to January 2023 at VRDL, Department of Microbiology, Diamond Harbour Government Medical College and Hospital. Serum was collected for IgM antibody enzyme-linked immunosorbent assay (ELISA) for scrub typhus (In bios kit) and Chikungunya (NIV Chikungunya IgM Capture ELISA Kit) test. Four hundred and eighty-seven samples were tested for IgM antibody by chikungunya and scrub typhus ELISA kit. Result: The present study demonstrated that, from the month of August 2022 to January 2023, 67% of chikungunya cases, 25% cases with only scrub typhus, and 8% cases with both chikungunya and scrub typhus presented positive. A present study shows that chikungunya is slightly more prevalent in males as compared to females, where scrub typhus is equally positive in both male and female patients. Conclusion: Laboratory testing of both of the diseases can prevent the complication of other suspected disease in coinfected patients.